The p‐EVES study design and methodology: a randomised controlled trial to compare portable electronic vision enhancement systems (p‐EVES) to optical magnifiers for near vision activities in visual impairment. (13th August 2014) - Taylor, John; Bambrick, Rachel; Dutton, Michelle; Harper, Robert; Ryan, Barbara; Tudor‐Edwards, Rhiannon; Waterman, Heather; Whitaker, Chris; Dickinson, Chris
Abstract Purpose To describe the study design and methodology for the p‐EVES study, a trial designed to determine the effectiveness, cost‐effectiveness and acceptability of portable Electronic Vision Enhancement System (p‐EVES) devices and conventional optical low vision aids (LVAs) for near tasks in people with low vision. Methods The p‐EVES study is a prospective two‐arm randomised cross‐over trial to test the hypothesis that, in comparison to optical LVAs, p‐EVES can be: used for longer duration; used for a wider range of tasks than a single optical LVA and/or enable users to do tasks that they were not able to do with optical LVAs; allow faster performance of instrumental activities of daily living; and allow faster reading. A total of 100 adult participants with visual impairment are currently being recruited from Manchester Royal Eye Hospital and randomised into either Group 1 (receiving the two interventions A and B in the order AB), or Group 2 (receiving the two interventions in the order BA). Intervention A is a 2‐month period with conventional optical LVAs and a p‐EVES device, and intervention B is a 2‐month period with conventional optical LVAs only. Results The study adopts a mixed methods approach encompassing a broad range of outcome measures. The results will be obtained from the following primary outcome measures: Manchester Low Vision Questionnaire, capturing device 'usage' data (which devices are used, number of times, for what purposes, and for how long) and the MNRead test, measuring threshold print size, critical print size, and acuity reserve in addition to reading speed at high (≈90%) contrast. Results will also be obtained from a series of secondary outcome measures which include: assessment of timed instrumental activities of daily living and a 'near vision' visual functioning questionnaire. A companion qualitative study will permit comparison of results on how, where, and under what circumstances, p‐EVES devices and LVAs are used in daily life. A health economic evaluation will provide results on: the incremental cost‐effectiveness of p‐EVES compared to optical magnifiers; cost‐effectiveness; and cost‐utility. Conclusions The evidence base in low vision rehabilitation is modest and further high quality clinical trials are required to inform decisions on healthcare provision. The p‐EVES study findings are anticipated to contribute to this broader evidence requirement, with the methodological issues evident here being relevant to other trials within the field.